2013
DOI: 10.1007/s00253-013-4890-1
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous protein secretion by Candida utilis

Abstract: The yeast Candida utilis (also referred to as Torula) is used as a whole-cell food additive and as a recombinant host for production of intracellular molecules. Here, we report recombinant C. utilis strains secreting significant amounts of Candida antarctica lipase B (CalB). Native and heterologous secretion signals led to secretion of CalB into the growth medium; CalB was enzymatically active and it carried a short N-glycosyl chain lacking extensive mannosylation. Furthermore, CalB fusions to the C. utilis Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 36 publications
1
43
1
Order By: Relevance
“…The first transformation system for C. utilis was described by Kondo et al (1995), who used an integrative transformation vector expressing a gene encoding a mutated ribosomal protein L41 conferring cycloheximide resistance as dominant selection marker. In the following years, other dominant markers including heterologous genes aph, hph, nat, and ble genes (conferring resistance to G418, hygromycin B, nourseothricin, or zeocin, respectively [Shimada et al 1998;Kunigo et al 2013;Boňková et al 20 14]) and end oge nou s ge ne YA P 1 (conferr ing cycloheximide-resistance [Iwakiri et al 2005b]) were added for selection of transformants. Antibiotic-resistance markers were used to generate specific mutations in the C. utilis genome by homologous recombination with a disruption cassette encompassing the dominant marker gene.…”
Section: Recombinant Dna Toolsmentioning
confidence: 99%
See 4 more Smart Citations
“…The first transformation system for C. utilis was described by Kondo et al (1995), who used an integrative transformation vector expressing a gene encoding a mutated ribosomal protein L41 conferring cycloheximide resistance as dominant selection marker. In the following years, other dominant markers including heterologous genes aph, hph, nat, and ble genes (conferring resistance to G418, hygromycin B, nourseothricin, or zeocin, respectively [Shimada et al 1998;Kunigo et al 2013;Boňková et al 20 14]) and end oge nou s ge ne YA P 1 (conferr ing cycloheximide-resistance [Iwakiri et al 2005b]) were added for selection of transformants. Antibiotic-resistance markers were used to generate specific mutations in the C. utilis genome by homologous recombination with a disruption cassette encompassing the dominant marker gene.…”
Section: Recombinant Dna Toolsmentioning
confidence: 99%
“…Correct genomic integration in the desired locus has not been verified extensively in all cases, but the availability of the whole genome sequence should ameliorate this situation in the future. Multiple plasmid integrations have been reported for the rDNA and URA3 loci (Kondo et al 1997), while single-plasmid integrations were reported for the TDH3 and HIS3 loci (Kunigo et al 2013. For unknown reasons, high plasmid copy numbers were found to occur by integration at the URA3 locus (reported up to 90 copies); this property was exploited in a Bcocktail multicopy integration method^to randomly integrate different expression units at this site (Tamakawa et al 2013b).…”
Section: Recombinant Dna Toolsmentioning
confidence: 99%
See 3 more Smart Citations